Clinic of Mathematics with the PPLAM Approach: Efforts to Improve Students’ Mathematics Learning in Manokwari - Lubis, Loria Amisah; Trigarcia Maleachi Randa; Esther Ria Matulessy; Chrisaria Palungan; Dahlia Gladiola Rurina Menufandu (Department of Mathematics, Faculty of Mathematics and Natural Sciences, Universitas Pamulang, Indonesia, 2026)
This study aims to analyze the effectiveness of the Mathematics Clinic in overcoming the difficulties of seventh-grade junior high school students in integer operations. The research focused on improving students’ learning outcomes through a short learning intervention consisting of a pretest, structured practice, and a posttest conducted within a single day. The method employed was a quasi-experimental design with a one-group pretest–posttest dengan Embedded Learning Analytics (PPLAM). The subjects were 25 seventh-grade students purposively selected based on their identified difficulties in learning mathematics. Data were collected through achievement tests (pretest and posttest) and students’ practice records. The data analysis included a paired t-test to measure the difference between pretest and posttest scores, the calculation of Normalized Gain (N-Gain) to assess the effectiveness of improvement, and effect size to determine the magnitude of the intervention’s impact. In addition, a simple learning analytics approach was applied to examine the relationship between practice quality and posttest results. The findings revealed a significant improvement in students’ learning outcomes with . The mean N-Gain score of 0.578 indicated a medium level of improvement, while the effect size (Cohen’s d = 2.164) was categorized as very large. Furthermore, learning analytics analysis showed an R2 = 0,70 suggesting that practice quality positively contributed to students’ posttest performance. It can be concluded that the Mathematics Clinic is effective as an alternative learning strategy to address difficulties in integer operations, even when implemented within a short time frame.